The Implementation Model for Creating Young Entrepreneurs Based on Bengkalis Local Business Potentials Through Industrial Incubator Based Learning - Raflah, Wan Junita; Hendri, John; Ananda, Faisal; Sari, Evi Permata (Politeknik Negeri Bengkalis, 2024)
This research aims to analyze a model to create young entrepreneurs in Bengkalis. This study analyzed the roleof business incubator and the potential of local businesses in Bengkalis to develop a model for creating young entrepreneurs.The analysis method used a mix method, which combines descriptive qualitative analysis and quantitative analysis.Descriptive qualitative analysis is used to explain the perceptions of respondents through questionnaires. Quantitativeanalysis uses Structural Equation Modelling - Partial Least Square (SEM-PLS) to identify the roles of Industrial IncubatorBased Learning and Local Business Potentials to Create Young Entrepreneurs. The research results suggest that there ispotential for further development of prospective local businesses, even though the number of young entrepreneurs relativelysmall. The development of local businesses with greater support and resources potentially foster greater entrepreneurialinterest among young people. This research also found that The efforts by local governments and higher educationinstitutions to advance MSMEs have yet to reach their full potential. In addition, collaborative industrial incubator basedlearning has been introduced as an integrated learning framework to create young entrepreneurs in Bengkalis.